Fast Mapping Across Time: Memory Processes Support Children’s Retention of Learned Words - Vlach, Haley; Sandhofer, Catherine M. (Frontiers in Psychology, 2012)
Children’s remarkable ability to map linguistic labels to referents in the world is commonly called fast mapping. The current study examined children’s (N = 216) and adults’ (N = 54) retention of fast-mapped words over time (immediately, after a 1-week delay, and after a 1-month delay). The fast mapping literature often characterizes children’s retention of words as consistently high across timescales. However, the current study demonstrates that learners forget word mappings at a rapid rate. Moreover, these patterns of forgetting parallel forgetting functions of domain-general memory processes. Memory processes are critical to children’s word learning and the role of one such process, forgetting, is discussed in detail – forgetting supports extended mapping by promoting the memory and generalization of words and categories.